Sudden Infant Death Due to Postvaccinal Myocarditis: A Case Report - Salahshour, Babak; Sadeghi, Sajjad; Sajadianfar, Ahmad; Soltaninejad, Kambiz (International Journal of Medical Toxicology and Forensic Medicine, 2021)
Background: Vaccination is a fundamental strategy in public health for controlling and eradicating infectious diseases. However, the undesirable Adverse Events Following Immunization (AEFI) should be effectively monitored, prevented, and managed in societies. Previously, Sudden Infant Death (SID) has been reported as a serious AEFI. We present a rare case of SID in an 18-month-old girl due to severe myocarditis following vaccination. Case Presentation: An 18-month-old girl presented to the Emergency Department (ED) with a history of the injection of Diphtheria-Tetanus-Whole Cell Pertussis (DTwP); Measles, Mumps, and Rubella (MMR), and oral poliovirus vaccines. She expired one-hour post ED admission after the episodes of vomiting and cardiopulmonary arrest. Postmortem histopathological examination signified marked congestion and the destruction of muscle fibers in the myocardium with inflammatory cells infiltration predominantly eosinophils. Given the postmortem histopathological findings, the cause of death was concluded as severe myocarditis following vaccination. Finally, the causality assessment was performed according to the Naranjo scale; the relevant data revealed a probable association in this regard (Naranjo score 6). Conclusion: Myocarditis is a rare and probable AEFI; thus, cardiac monitoring should be recommended as a diagnostic measure in managing postvaccinal adverse effects.